Level of Patient Satisfaction with Communication, Information and Drug Education Services by Pharmacy Personnel at the Bulang Community Health Center, Batam City - Hainil, Sri; Gusmali, Desy Maniarti; Utami, Rury Trisa; Meilanda, Rastria; Pannida, Putri Ramas (Formosa Journal of Sustainable Research, 2025)
Drug communication, information, and education (KIE) services are a form of pharmaceutical service in the form of delivering important things about drugs obtained by patients from the pharmacy installation when dispensing drugs, patient satisfaction is a benchmark for patients to determine the perception of the performance of pharmaceutical personnel has met or exceeded patient expectations from the services provided. The purpose of this study was to determine the level of patient satisfaction with drug IEC services by pharmaceutical personnel at the Bulang Health Center, Batam City. This type of research is a descriptive survey, the sampling method is purposive sampling with a total of one hundred patients and using a research instrument in the form of a questionnaire that has been validated and reliable. There are five categories of satisfaction dimensions used to measure the level of patient satisfaction with drug IEC services at Bulang Health Center, namely the dimensions of reliability, responsiveness, assurance, empathy, and tangible. Data was processed using a Likert scale and then analyzed using univariate analysis and the results of the study showed that Bulang Health Center obtained results of reliability 74% felt satisfied, responsiveness 50% felt quite satisfied, assurance 55.6% felt quite satisfied, empathy 60% felt quite satisfied, tangible 61% felt satisfied